Ferroelectric-field accelerated charge transfer in 2D CuInP₂S₆ heterostructure for enhanced photocatalytic H₂ evolution - Lin, Bo (2022)
The development of ferroelectric photocatalytic materials with polarization electric field is a key approach to realize the spatial separation and fast transfer of charge carriers in visible-light-driven H2 evolution. Generally, replacing traditional 3D perovskite-type ferroelectric materials with 2D ferroelectric materials is disregarded as candidates for photocatalysis. Herein a 2D CuInP2S6 (CIPS) with room-temperature ferroelectricity (a Curie temperature of around 47 °C) is developed as a new photocatalyst, and 2D/2D heterojunction of CuInP2S6 nanosheet/g-C3N4 ultrathin flake (CIPS/CN) is constructed to further accelerate charge transfer. Benefitting from the synergetic action of the inner polarization electric field of CIPS and 2D/2D heterojunction, CIPS/CN displays a substantially accelerated charge transfer and significantly enhanced photocatalytic H2 evolution rate, which is up to 7.6 times by contrast with that of paraelectric-phase CIPS. This work would provide a new platform for the design of 2D ferroelectric photocatalytic system with highly-efficient charge transfer.